Establishing the Effects of Growth Regulators on Melon Seeds and Plants (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
The article describes the effect of nanosilicon preparations and microparticles used in melons on the growth, development and productivity of plants.